Branding yourself : how to use social media to invent or reinvent yourself - Deckers, Erik; Lacy, Kyle ([?] Pearson education, 2018)
Want a new job or career? Need to demonstrate more value to customers or employers? Use today's hottest social media platforms to build the powerful personal brand that gets you what you want! In this completely updated book, Erik Deckers and Kyle Lacy help you use social media to and networking to advance your career, grow your business, and land new job opportunities. From LinkedIn to Facebook, now including Instagram and SnapChat, this book is packed with new techniques and ideas that are practical, easy, and effective. Deckers and Lacy show you how to supercharge all your business and personal relationships...demonstrate that you are the best solution to employers' or partners' toughest problems...become a recognized thought leader...and turn your online network into outstanding jobs, great projects, and a fulfilling, profitable career!
I Why should I care about self-promotion : Welcome to the party ; How do you fit in the mix? -- II Your network is your castle-build it ; Blogging : telling your story ; LinkedIn : networking on steroids ; Twitter : sharing in the conversation ; Facebook : developing a community of friends ; Say cheese : sharing photos and videos ; Other social networking tools ; Googling yourself : finding yourself on search engines ; Bringing it all together : launching your brand ; Measuring success : you like me, you really like me! -- III Promoting your brand in the real world : How to network : hello, my name is ... ; Public speaking : we promise you won't die ; Getting published : I'm an author ! ; Personal branding : using what you've learned to land your dream job.
Includes bibliographical references and index.
Keywords: Business networks; Branding (Marketing); Career development; Social media; Branding (Marketing); Business networks; Career development; Social media